Arm swing analysis during transition of a heavier ten-pin bowling ball - Lim, Edina Yan Yi (2018)
Tenpin Bowling is a target based indoor sport whereby the goal is to roll a ball down the lane to drop all 10 pins to achieve a strike. This involves selection of appropriate bowling equipment and execution of appropriate technique. Keeping a consistent arm swing between bowls contributes to a more consistent ball release that increase the probability of a strike. Transferring more force to the ball also increases the chances of a strike due to more forceful impact of the pins. All developmental bowlers get to a stage in their career whereby coaches would ask them to increase their ball weight up to a maximum of 16 pounds. This is in anticipation that a heavier ball would result in increased revolutions and force at impact of the pins that should translate to a higher potential for strikes. These decisions are currently made without objective data and an understanding of the potential trade-off between the consistency of the arm swing, and swinging and subsequently rolling a heavier compared with lighter bowling ball. The purpose of this project was to compare the 3D kinematics of the arm swing when a bowler bowled with a ball that was 1 weight class (1 pound) higher compared with what he/she was used to. A three-dimensional (3D) motion analysis system was used to capture the 3D kinematics of the arm swing of one bowler performing 10 bowls with the weight that they were used to and 10 bowls with a ball that was one weight class higher. However, only 5 trials, with a strike, for each condition (weight of the bowling ball) will be analyzed. Signal processing and musculoskeletal modeling was performed to obtain kinematics and kinetics of the shoulder, elbow joint and wrist joint. In conclusion, it was found that with the difference in bowling ball weight condition, there are no differences in arm motion. However, there was inconsistency between 5 phases of the bowling arm swing. Lastly, we have also attempted to measure the velocity of the bowling ball during bowling and concluded that it is possible to obtain kinetics data, such as bowling ball velocity; of the bowling ball provided there are four extreme ends of markers.